ANTIHYPERTENSIVE ACTIVITY ETHANOLIC EXTRACT OF BULB ELEUTHERINE AMERICANA MERR ON FRUCTOSE-INDUCED HYPERTENSION RATS - Hasimun, Patonah; Zakaria, Hasballah; Susilawati, Elis; Wardiono, Jeany Dwiyulia (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study aimed to evaluate ethanolic extract of bulb of Eleutherine americana Merr as antihypertensive. Methods: This study examined the effect of ethanol extract of bulb of Eleutherine americana Merr on urine volume, blood pressure, and electrocardiogram (ECG) profile. Diuretic activity was evaluated by the Lipschitz method. Furosemide (3.6 mg/kg) used as standard drug. Animal rats model of hypertension were induced by fructose 66% in the diet for 21 d. Captopril (2.5 mg/kg) used as standard antihypertension. Parameters measured were urine volume for 24 h, systolic and diastolic blood pressure, and electrocardiogram profile. Results: High fructose diet for 21 d reduced R-R, P-R interval of the electrocardiogram, increased systolic and diastolic blood pressure and heart rate compared to normal group statistically significant (p<0.05). Animals received an ethanolic extract of the bulb of Eleutherine americana Merr doses of 25, 50, 100 mg/kg showed lowered systolic and lowered diastolic blood pressure (except for a dose of 100 mg/kg). Dose of 25, 50 mg/kg lowered systolic blood pressure was comparable to captopril 2.5 mg/kg (p>0.05). The group received a dose of 100 mg/kg showed diuretic activity comparable to furosemide 3.6 mg/kg (p>0.05). The group received a dose of 25, 50, 100 mg/kg, showed improved on R-R, P-R interval of the electrocardiogram, and heart rate. Conclusion: It can be concluded that ethanolic extract of bulb Eleutherine americana Merr play important role in regulating blood pressure, increased urine volume and improved electrocardiogram profile.